HPV distribution in cervical cancer in Portugal. A retrospective study from 1928 to 2005 - Félix, Ana (Papillomavirus Res, 2016)
OBJECTIVES: To determine human papillomavirus (HPV) types in invasive cervical cancer in Portugal. METHODS: Cases diagnosed at the Instituto Português de Oncologia de Lisboa de Francisco Gentil from the year 1928 to 2005 were selected for HPV DNA detection and genotyping using SPF10/DEIA/LiPA25 system. RESULTS: Of the 1214 samples that were considered appropriate for HPV detection, 714 (58.8%; 95% CI: 56.0–61.6%) were positive for HPV DNA. This detection rate varied being lower in the first 3 decades (31.3%; 50.1%; 46.5%) and higher in the last decades (77.4–95.1%). This difference was due probably to the fixative used in the first three decades. The five most common types identified among HPV positive cases were HPV16 (58.2%), HPV18 (9.2%), HPV33 (6.2%), HPV45 (4.7%) and HPV31 (4.4%). Multiple infections were detected in 2.8% of the cases. HPV16 and 18 accounted for 67.4% of infections. There were no statistically significant changes of these types over the studied period. An increase at patient׳s age at diagnosis was observed in the last decades (p<0.001). CONCLUSION: HPV16 and 18 accounts for almost 70% of cervical cancers in all 9 decades studied and support data that effective vaccination against these 2 types will reduce the cervical burden in Portuguese women.